3D flower-like MOF-derived NiCo-LDH integrated with Ti3C2Tx for high-performance pseudosupercapacitors. (20th April 2021) - Wang, Yanzhong; Shi, Chenjing; Chen, Yanjun; Li, Dan; Wu, Guangping; Wang, Chao; Guo, Li
Highlights: 3D flower-like NiCo-LDH/Ti3 C2 Tx is prepared by ion-exchange reaction of ZIF-67/ Ti3 C2 Tx . NiCo-LDH/Ti3 C2 Tx electrodes have a high capacitance of 635.7 C g −1 at 1 A g −1 . The asymmetrical supercapacitor show high energy density of 44.6 Wh kg −1. The capacitance retention of device is 85.71% after 10, 000 cycles. Abstract: Nickel cobalt layer double hydroxides (NiCo-LDH) have high theoretical capacity for energy storage, but suffer from low electrical conductivity and sluggish charge transfer kinetics. Herein, three-dimensional (3D) porous flower-like NiCo-LDH/Ti3 C2 Tx is facilely fabricated via the electrostatic self-assembly of metal-organic frameworks and Ti3 C2 Tx followed by the ion-exchange reaction. The as-prepared NiCo-LDH/Ti3 C2 Tx -5 delivers a high specific capacity of 635.7 C g −1 at 1 A g −1, and still remains 382.3 C g −1 at 20 A g −1 . Furthermore, the corresponding asymmetric supercapacitor coupled with activated carbons achieves high energy density of 44.6 W h kg −1 under the power density of 852.5 W kg −1, and indicates remarkable cycling performance (85.71% of capacitance retention after 10, 000 cycles). The outstanding electrochemical performance is assigned to 3D porous structure and high electrical conductivity, which not only increases the contract area between electrodes and electrolyte, but also enhances the ion diffusion and charge transfer kinetics. Graphical abstract: The as-prepared NiCo-LDH/Ti3 C2 Tx -5 delivers a high specific capacity of 635.7 C g −1 at 1 A g −1, and still remains 382.3 C g −1 at 20 A g −1, indicating the excellent rate capability. Image, graphical abstract